Genome sequence of Streptomyces pluripotens MUSC 135(T) exhibiting antibacterial and antioxidant activity - Ser, Hooi Leng; Tan, Wen Si; Ab Mutalib, Nurul Syakima; Cheng, Huey Jia; Yin, Wai Fong; Chan, Kok Gan; Lee, Learn Han (Elsevier, 2015)
Isolated from intertidal soil, Streptomyces pluripotens MUSC 135(T) produces a broad-spectrum bacteriocin against the pathogens methicillin-resistant Staphylococcus aureus (MRSA) ATCC BAA-44(T), Salmonella typhi ATCC 19430(T) and Aeromonas hydrophila ATCC 7966(T). Along with antibacterial activity, fermentation studies on strain MUSC 135(T) revealed production of antioxidant(s). The high quality draft genome of MUSC 135(T) comprises 7,480,269 bp with G + C content of 70.00%. Through bioinformatics analysis, 72 gene clusters identified in the genome were associated with the production of secondary metabolites, which may shed light on the identity of these bioactive compounds. (c) 2015 Elsevier B.V. All rights reserved.